Integration of Environmental Education into Natural and Social Sciences Subjects for Fourth-Grade Elementary School in Makassar City - Pertiwi, Nurlita; Sahabuddin, Erma Suryani; Taufieq, Nur Anny Suryaningsih (Indonesian Journal of Educational Studies, 2024)
Abstract. This research aims to assess the environmental education integration model's effectiveness in improving elementary school students' knowledge and attitudes in science subjects. Efforts to integrate environmental education with subjects in elementary schools have developed to emphasize the importance of student knowledge development. However, limitations in time and learning achievement targets require carefully designed integration methods. This study is an experiment that applies the integration of Environmental Education (EE) with science lessons through video media and class discussions. This research is classified as quantitative research with a quasi-experimental approach. The population of this study consisted of 4th-grade elementary school students in Makassar City. The data analysis technique used was the pretest-posttest group design, and hypothesis testing was analyzed using the Paired Sample T-Test. The results of this study indicate that there is potential to support the integration model. Environmental Education integration material was selected by reviewing the science lesson planning documents and searching for relevant environmental issue news on electronic media. The findings revealed differences in students' knowledge and attitudes before and after receiving environmental education through the integration of science learning. The changes in students’ environmental knowledge and attitudes were also significantly different before and after the environmental education was provided.